2020
DOI: 10.1080/21645515.2019.1666612
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of anti-HBs after hepatitis B vaccination among adults: 8-year results

Abstract: The long-term persistence of hepatitis B surface antibody (anti-HBs) after hepatitis B vaccination among adults was not known clearly. This study aimed to assess the immunogenicity and persistence of antibodies 8 years after hepatitis B immunization with different vaccination schedules among adults who tested negative for hepatitis B surface antigen (HBsAg), anti-HBs, and hepatitis B core antibody (anti-HBc). A total of 771 participants who received the full vaccination course (three doses) and also had a bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
4
13
0
1
Order By: Relevance
“…In a recent systematic review, the different vaccination schedule obtain the similar short-term immune effect, demonstrating that anti-HBs concentrations ≥ 10 m IU/ml were approximately 65.0-85.0% using the 0-1-2-months schedule, approximately 77.0-90.8% using the 0-7-21-day schedule, 87.0% using the 0-2-6-week schedule, and around 79.0% after the 0-14-28-day schedule, respectively. 22 Ren et al 18 also reported that the accelerated schedule (0-1-3-months) and the standard schedule (0-1-6 months) enhanced the long-term immune memory (8 years after) in comparison to (0-1-12-months) schedule, which we found a similar long-term immune effect in the present study (2 years after). Regarding the short-term immune effect, we speculate that the different short-term immune effect may be explained by that the measurement was taken at a different time (4th months for "0-1-3-months", 7th months for "0-1-6-months" and 13th months for "0-1-12-months), since the 6-months and 12-months injection serve as a booster dose, which was known to increase the seroconversion rate.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In a recent systematic review, the different vaccination schedule obtain the similar short-term immune effect, demonstrating that anti-HBs concentrations ≥ 10 m IU/ml were approximately 65.0-85.0% using the 0-1-2-months schedule, approximately 77.0-90.8% using the 0-7-21-day schedule, 87.0% using the 0-2-6-week schedule, and around 79.0% after the 0-14-28-day schedule, respectively. 22 Ren et al 18 also reported that the accelerated schedule (0-1-3-months) and the standard schedule (0-1-6 months) enhanced the long-term immune memory (8 years after) in comparison to (0-1-12-months) schedule, which we found a similar long-term immune effect in the present study (2 years after). Regarding the short-term immune effect, we speculate that the different short-term immune effect may be explained by that the measurement was taken at a different time (4th months for "0-1-3-months", 7th months for "0-1-6-months" and 13th months for "0-1-12-months), since the 6-months and 12-months injection serve as a booster dose, which was known to increase the seroconversion rate.…”
Section: Discussionsupporting
confidence: 88%
“…12,13 Such accelerated immunization schedules ( 0-1-2-months, 0-1-3-months and 0-7-21-days, etc.) were veri ed to have the same short-term immune effect and to increase the completion rate in the general population 14 , vein-injected drug users 15,16 and adults who were refused to receive the second or third dose owing to occupational reasons 17,18 . However, antibody maintenance by immune memory was even more crucial than antibody production in protecting patients from HBV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatitis B vaccine has been proved very effective at preventing infection with HBV [6,7]. Currently, the recombinant hepatitis B vaccine is widely used in China for immunization; it can be classified as Hansenula (HepB-HP), Saccharomyces cerevisiae (HepB-SC) and Chinese hamster ovary cells (HepB-CHO), and the dosage forms can be classified as 5 µg/dose, 10 µg/dose, 20 µg/dose and 60 µg/dose.…”
Section: Introductionmentioning
confidence: 99%
“…Several long-term studies of immune persistence have shown that the anti-HBs ≥ 10 mIU/mL proportion of adults immunized with hepatitis B vaccine after 20-30 years was 50-60%, but booster immunization was not recommended [14][15][16]. However, in China, according to a cohort study, the seroprotection rate of adult vaccination against hepatitis B was reduced to 58.3% after eight years [7].…”
Section: Introductionmentioning
confidence: 99%